European Banking Reform Should Embrace a Unitary Approach to Failed Banks - Anna Gelpern; Nicolas Véron (CESifo Forum, 2021)
Six years after starting the banking union, the European Union has reiterated its members' commitment to "make further concrete progress on the Banking Union by the end of the year" (Donohoe 2020). EU officials are right not to let Covid-19 derail necessary debates over this objective. But the reinvigorated discussion has become increasingly confused when it comes to dealing with failed banks. There is a danger that the EU could cite experience with the US Federal Deposit Insurance Corporation (FDIC) to make its already fragmented regime even more fragmented. That would be a mistake. A closer look at the FDIC model highlights the value of a unitary process for resolving all deposit-taking banks, no matter how large or small.
Keywords: 330